Effects of stellate ganglion block on perimenopausal hot flashes: a randomized controlled trial - Li, Ying; Chang, Jia; Shi, Gaoxiang; Zhang, Wenjing; Wang, Hui; Wei, Lingyun; Liu, Xiaochun; Zhang, Weiwei (Frontiers in Endocrinology, 2023)
Hot flashes are common symptoms afflicting perimenopausal women. A stellate ganglion block (SGB) is believed to be an effective treatment for hot flashes; however, more evidence is needed to evaluate its safety and efficacy in relieving perimenopausal hot flashes.To investigate the efficacy and safety of SGB for the treatment of perimenopausal hot flashes.A randomized controlled trial was conducted at Shanxi Bethune Hospital. Forty perimenopausal women with hot flashes were recruited from April 2022 to November 2022 and randomly assigned to receive either 6 consecutive SGB treatments or 6 consecutive saline placebo treatments. The primary outcome was the change in hot flash symptom score from baseline to 12 weeks after treatment. The secondary outcomes were the change in hot flash symptom score from baseline to 12 weeks after treatment and the post-treatment Kupperman Index (KI) and Pittsburgh Sleep Quality Index (PSQI) scores.Of the 40 randomized subjects, 35 completed the study. All the variables were significantly improved. During 12 weeks of follow-up, the hot flash scores, Kupperman Menopause Scale scores, and Pittsburgh Sleep Quality Scale scores decreased significantly. Two subjects in the SGB treatment group experienced transient hoarseness, and the incidence of related adverse events was 10%. No related adverse events occurred in the control group.Compared to the control treatment, SGB treatment was a safe and effective nonhormone replacement therapy that significantly relieved perimenopausal hot flashes and effectively improved sleep quality. Additional studies are needed to assess the long-term efficacy of this therapy.